Pemanfaatan Barcode Scanner Pendaftaran Pasien Pada Puskesmas Rawat Inap Way Kandis - Didi Susianto; Eka Ridhawati; Yuli Syafitri (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2021)
Way Kandis Inpatient Health Center as a provider of health care facilities are required to provide fast and accurate health services. The problem currently faced is patient service which includes patient registration, patient data processing, and report data processing which is still done manually so that it is ineffective and slows down or complicates registration officers in serving patients. The system development method used by the author for this research is the Extreme Programming method, while the process of making this system uses the PHP programming language, while the database uses MySQL. The design tool uses a UML diagram that consists of use case diagrams, class diagrams, and activity diagrams. From this research, a barcode scanner based on patient registration information system is produced which is able to process registration data, print queue evidence, process patient data, print barcode patients, and process reports better than the old system. The system built can simplify and help to improve the performance of registration officers in serving patients at Way Kandis Inpatient Health Center quickly, and accurately.